Toxicological Effects of Commonly Used Mosquito Coil Smoke on Liver and Lung Function in Rats - Hadiza Abubakar; Yahuza Gimba Muhammed; Alhassan Muhammad Wudil; Dayyabu Shehu; Murtala Yaú (QAASPA Publisher, 2024)
The utilization of mosquito coils as a household-level strategy for mosquito control is widely practiced in malaria-endemic regions spanning Africa, Asia, and South America. However, the continuous application of mosquito coils has prompted significant apprehensions concerning environmental and health implications. This research aims to evaluate the potential hepatic and pulmonary toxicities associated with the inhalation of mosquito coil smoke in rat subjects over both sub-chronic and chronic durations. A questionnaire was used to make inquiries regarding the prevalent types and brands of mosquito coils employed, the manner in which they are used, the durations for which they are utilized. A total of twenty-four albino rats were categorized into three distinct groups: the control group and two exposed groups. These groups were subjected to distinct brands of mosquito coil smoke across two distinct exposure regimens - a sub-chronic exposure lasting 4 weeks and a chronic exposure spanning 12 weeks. Following the exposure periods, blood samples were collected for the analysis of serum-based and biochemical markers, including serum aspartate aminotransferase (AST), alanine aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), bilirubin, serum bicarbonate, and Lactate dehydrogenase (LDH), oxygen saturation, C-reactive protein, total protein, and microscopic analysis of lung tissue and liver tissue. The histopathological analysis of lung tissue was appropriately included. However, the analysis of liver tissue was omitted. The results demonstrated a significant elevation in the levels of these biochemical markers among the exposed rats in comparison to the control group. Concurrently, a decrease in blood oxygen saturation was noted in the exposed rats when contrasted with the control group. Conversely, the serum concentrations of high-sensitivity C-reactive protein, total protein, and alanine aminotransferase (ALT) did not exhibit notable differences in relation to the control group. Additionally, microscopic analysis of lung tissue indicated the presence of histopathological lesions in the exposed rats, suggesting a detrimental impact of mosquito coil smoke exposure in a time-dependent progression.